Chemical modification of activated carbons and its effect on the adsorption of phenolic compounds (2015)
(Eng) In this paper two commercial activated carbons, granular and pelletized, were impregnated with aqueous solutions of phosphoric acid (H3PO4), or potassium hydroxide (KOH) in 60% w/w concentrations under moderate temperature conditions (18 °C). It was observed that the impregnation with phosphoric acid increases the adsorption of 2,4-dinitrophenol regarding the starting activated carbon. The adpsorption was determined from isotherms in aqueous solution of phenol and 2,4-dinitrophenol, and experimental data were adjusted to the Freundlich, Langmuir, Toth and Prausnitz-Radke models. Langmuir was the model that best fitted for phenol adsorption, and Toth was the model that best fitted the for 2,4-dinitrophenol adsorption. The results showed that the impregnation of activated carbons without post further heating continued creating changes in surface chemistry and porous structure.